PENGARUH MINAT BELAJAR TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 19 MERANGIN - Lidia Oktaviani; Awatif; Hasmawati (Hira Institute, 2025)
This study aims to characterize the vital relationship between scientific concept information and learning motivation. This approach to employment considers a quantitative perspective, with the strategy employed being correlational. The testing strategy employs a stratified sampling approach, since the population is less than 100, and the test in this study involves 57 respondents. The consider was conducted with a survey instrument and test questions, where the number of articulations within the survey is 30 things and the number of scientific concept understanding test questions is 5 things within the shape of papers. Based on the examination, both information are regularly disseminated and have a straight design, so the theory test employments the Item Minute relationship test strategy, for the noteworthiness test utilizing the Z-test, beginning with a outline of the determinant coefficient to decide the relative greatness of the alter of variable X in connection to the variable Y. Besides, a basic direct relapse test and a relapse noteworthiness test were carried out. Based on the comes about of information investigation, it appears that Fcal > Ftable or 2,515,226 > 4.02, then H0 is rejected and H1 is acknowledged, which implies that there's a noteworthy impact between learning intrigued on the understanding of scientific concepts of review VIII understudies at SMP Negeri 19 Merangin for the 2024/2025 Scholastic Year, with a commitment of 40.96%.